2017
DOI: 10.1371/journal.pone.0189035
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different anti-vascular endothelial growth factor treatment regimens on reducing burden for caregivers and patients with wet age-related macular degeneration in a single-center real-world Japanese setting

Abstract: ObjectiveTo describe the burden associated with different anti-vascular endothelial growth factor (VEGF) treatment strategies for wet age-related macular degeneration (wAMD) in a real-word setting in Japan.MethodsSingle-center, cross-sectional survey of caregivers of patients with wAMD performed in a hospital in Mito-City, a rural area in Japan. Caregiver burden was evaluated using the Burden Index of Caregivers (BIC-11), and depressive symptoms were assessed by the Center for Epidemiologic Studies Depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 24 publications
2
33
0
2
Order By: Relevance
“…Two studies reported on the cost savings associated with the use of anti-VEGF treatments in nAMD patients [ 42 , 43 ]. Windsor et al concluded that the use of optical coherence tomography (OCT)-guided anti-VEGF therapy (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported on the cost savings associated with the use of anti-VEGF treatments in nAMD patients [ 42 , 43 ]. Windsor et al concluded that the use of optical coherence tomography (OCT)-guided anti-VEGF therapy (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The total patient savings by using OCT-guided anti-VEGF therapy (based on a 20% copay for anti-VEGF therapy, and avoiding 17.7 million IVIs from 2008 to 2015) could amount to $2.2 billion. Hanemoto et al showed cost savings associated with the implementation of a proactive treat-and-extend (T&E) regimen when compared with as-needed dosing, mostly due to a reduction in hospital visits [ 42 ]. The T&E regimen was also associated with reduced caregiver burden.…”
Section: Resultsmentioning
confidence: 99%
“…However, these pivotal trials were based on monthly injections, which in real-life long-term settings are of significant burden for patients, caregivers, healthcare practitioners, and healthcare systems [11]. Alternative treatment regimens therefore emerged.…”
Section: Introductionmentioning
confidence: 99%
“…22 The dependence on a caregiver to accompany the patient and the financial cost of treatment also pose a burden on the patient. 23,24 This rapid review aims to identify and summarize the most recent information on the effectiveness of interventions to increase uptake and completion of treatment for DR and/or DMO in LMICs.…”
Section: Introductionmentioning
confidence: 99%